2005
DOI: 10.1142/s0192415x05002886
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation and Radioprotection byPropolis

Abstract: In this study, we focused on immune stimulation by Propolis, and examined changes in the effect of irradiation after Propolis administration. We also examined the radioprotective effect of Propolis by observing its effect on the immune system. The effect of immune activation by Propolis was investigated by measuring the total immunoglobulin (Ig) G and IgM. The radioprotective effect of immune activation by Propolis was investigated by measuring the T-lymphocyte subsets in the peripheral blood of mice following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…The relationship between propolis and the immune system has been recently reviewed [10], and past studies have identified correlations between its immune-modulating properties and the inhibition of tumour growth [15,40]. Furthermore, propolis has been found to alter cytokine patterns, to activate T-helper cells to proliferate and to stimulate cell-mediated immune responses [41], factors intimately connected with the protection of the T-cell-mediated immunity in the skin against photodamage [2]. It was therefore consistent to find that treatment with 100 mg/kg propolis reduced the SSUV-induction of IL-10, the cytokine most closely associated with the immunosuppressed state, but protected the expression of IL-12 from SSUV depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between propolis and the immune system has been recently reviewed [10], and past studies have identified correlations between its immune-modulating properties and the inhibition of tumour growth [15,40]. Furthermore, propolis has been found to alter cytokine patterns, to activate T-helper cells to proliferate and to stimulate cell-mediated immune responses [41], factors intimately connected with the protection of the T-cell-mediated immunity in the skin against photodamage [2]. It was therefore consistent to find that treatment with 100 mg/kg propolis reduced the SSUV-induction of IL-10, the cytokine most closely associated with the immunosuppressed state, but protected the expression of IL-12 from SSUV depletion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used since ancient times as a medicine (Hegazi, 1998) due to its biological properties as an antimicrobial (Hegazi et al, 2014a), antifungal (Hegazi et al, 2000), antiprotozoal (Hegazi et al, 2014b), antiparasitic (Hegazi et al, 2007a,b) and antiviral agent (Hegazi et al, 2012a;Fan et al, 2013), antioxidant (Abd El Hady et al, 2007), hepatoprotective (Gonzales et al, 1995), immunostimulating (Hegazi and Abd El Hady, 1994;Takagi et al, 2005), localized plaque psoriasis (Hegazi et al, 2013) and cytostatic (Banskota et al, 2001). The chemical composition of propolis appeared to be extremely complex and more than 300 compounds have been identified so far (Marcucci, 1995), the most important ones being polyphenols (Hegazi and Abd El Hady, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that dietary bioactive food components that interact with the immune response have considerable potential to reduce susceptibility to infectious diseases (Kogut, 2009). Several reports on the immunomodula-tory activities of water-soluble derivatives of propolis (WSDP) have been published (Orsi et al, 2000;Takagi et al, 2005;Fischer et al, 2007), but little is known about the effect of ethanolic extracts of propolis on the immunological variables in hens. Also, the long-term effect of propolis administration on the biochemical and physiological parameters of hens has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%